Revisiting the Revised CLSI Breakpoint for Detecting Fluoroquinolones Resistance in Salmonella - Thapa, Suchitra; Shrestha, Basudha; Manandhar, Sarita (Journal of Institute of Science and Technology, 2020)
Resistance towards fluoroquinolones and treatment failure is a matter of concern in enteric fever. The present study was undertaken to analyze the susceptibility pattern of Salmonella towards fluoroquinolones using 2006 and 2013 Clinical Laboratory Standards Institute (CLSI) breakpoint for interpretation and revisit the efficacy of Nalidixic acid resistance (NAR) as a phenotypic marker. A retrospective analysis of the zone of inhibition (ZOI) diameter data and minimum inhibitory concentration (MIC) data of 105 Salmonella was conducted. The ZOI diameter analysis showed that all isolates were susceptible to Ofloxacin and Ciprofloxacin using the previous 2006 ZOI breakpoint. However, with the revised 2013 breakpoint of Ciprofloxacin, the susceptibility percent dropped significantly and for Ofloxacin the breakpoint was not revised, so the percentage remained unchanged. The MIC analysis showed that all isolates were susceptible towards Ofloxacin and 97.14 % of isolates were susceptible to Ciprofloxacin using the previous 2006 MIC breakpoint, while the susceptibility decreased for both antibiotics with the revised 2013 MIC breakpoint. Statistically, the ZOI diameter of Nalidixic acid and MIC values of Ciprofloxacin and Ofloxacin was negatively correlated. To conclude, the revision of breakpoints addresses the problem of screening fluoroquinolones resistance but the emerging fluoroquinolones resistance situation is still a matter of concern in healthcare facilities of Nepal. Thus a reliable screening method is need of the hour as NAR cannot be considered a reliable marker to screen fluoroquinolones resistance